(untitled) (Human Resource Strategy and Practice, 2025)
Quiet quitting—employees’ strategic reduction of discretionary effort while maintaining contractual obligations—has emerged as a critical concern in organizational psychology. Yet empirical research remains largely Western-centric and private-sector focused. This study addresses these gaps through the first quantitative analysis of quiet quitting antecedents among Tunisian public servants, integrating Job Demands–Resources (JD-R), social exchange, and Conservation of Resources (COR) frameworks. Drawing on a context-sensitive perspective, the study conceptualizes quiet quitting as a rational adaptive response to sustained organizational imbalance rather than as an individual or generational deviation. Based on data collected from 124 Tunisian civil servants across multiple public sectors, hierarchical regression analysis (R2 = 0.52, ΔR2 = 0.44, p < 0.001) reveals organizational recognition (β = −0.34, p < 0.001) and workload (β = 0.23, p = 0.015) as dominant predictors, confirming their roles as core motivational resources and stress-inducing demands within the JD-R framework. Managerial support and organizational justice show expected directional trends (p ≈ 0.09) but limited direct effects, suggesting that their influence may be constrained by bureaucratic rigidity and centralized decision-making structures characteristic of public administration. Findings position quiet quitting as a form of psychological adjustment shaped by high job security and limited exit opportunities, rather than as individual deviance. Theoretically, results advocate greater contextualization of disengagement models by integrating institutional constraints and employment regimes. In practice, interventions should prioritize recognition systems and workload management to restore reciprocity, conserve employee resources, and sustain functional engagement within public-sector organizations.